2019
DOI: 10.3892/etm.2019.8101
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑mediated GAS1 downregulation promotes the proliferation of synovial fibroblasts by PI3K‑Akt signaling in osteoarthritis

Abstract: Hyperplastic synovial fibroblasts (SFs) serve a critical role in the pathogenesis of knee osteoarthritis (OA); however, the molecular mechanism involved in OA during synovial tissue hyperproliferation remains unclear. Growth arrest-specific gene 1 (GAS1), a cell growth repressor gene, was found to be downregulated in OASFs according to previous preliminary experiments. It was therefore hypothesized that reduced GAS1 expression may participate in the hyperproliferation of SFs in OA development, downstream of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…OA is a prevalent joint disease with progressive pain, and the pathogeny of the disease remains unclear [25]. In recent years, the research on OA pathogenesis and treatment has focused on molecular mechanisms involving lncRNAs and miRs [26,27]. This study was designed to gain novel insight into the mechanism of Gm37494 in OA progression with the involvement of miR-181a-5p and GABRA1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA is a prevalent joint disease with progressive pain, and the pathogeny of the disease remains unclear [25]. In recent years, the research on OA pathogenesis and treatment has focused on molecular mechanisms involving lncRNAs and miRs [26,27]. This study was designed to gain novel insight into the mechanism of Gm37494 in OA progression with the involvement of miR-181a-5p and GABRA1.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence revealed that miR-181a acted as a mediator of cartilage degeneration and participated in the promotion of inflammation and death in chondrocytes [18,34]. Another study also reported that miR-181a-5pdown-regulated growth arrest-specific gene 1 might be a mechanism of OA development [26]. More importantly, prior research elucidated that miR-181a-5p expression was high in IL-1β-treated C28/I2 cells and that ectopic miR-181a-5p neutralized the repressive impacts of circ_0020093 up-regulation on the inflammation and apoptosis of IL-1β-induced C28/I2 cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cdc20 is an activator of the anaphase-promoting complex, and is weakly expressed in osteoblasts but highly expressed in the osteocytes [ 37 ]. Gas1 is a cell growth repressor gene that serves as a suppressive regulator of cell growth and as a mediator of apoptosis [ 38 ]. Nrp2 is a family member of the neuropilins, and one of its isoform Nrp2b inhibits cultured cell proliferation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we screened out 9 up-regulated DEMs and 10 down-regulated DEMs by exploring overlapped DEMs in the PBL of internal samples and synovial tissue of GSE143514 database. Among those up-regulated DEMs, mir-34a-5p could play an important role in the cell progression of osteosarcoma and could induce chondrocyte apoptosis during OA progression [ 26 ]. A previous study reported that mir-138-5p could inhibit the apoptosis and inflammation of chondrocytes and regulate cartilage phenotype and osteogenesis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%